High-efficient electron collection capability of graded Al compositional GaN nanowire arrays cathode. (1st December 2020) - Liu, Lei; Lu, Feifei; Tian, Jian; Zhangyang, Xingyue; Lv, Zhisheng
Abstract: Based on the purpose of solving the "secondary absorption" of adjacent nanowires and the lateral emission in the GaN nanowire arrays (NWAs) cathode, an exponential-doping and graded Al compositional GaN NWAs photocathode is proposed, which could generate internal electric field to increase the quantum efficiency (QE) of top surface, and the introduction of an external electric field promote the side-emission electrons to shift toward the collecting side. The QE and collection efficiency (CE) of exponential-doping and graded compositional GaN NWAs under different array structure parameters, incident angles and external electric field intensities are analyzed. The results show that although the collection ratio of emitted electrons in the exponential-doping GaN NWAs is higher, the graded Al compositional photocathode with a stronger built-in electric field can obtain better CE under the application of an external electric field, and the peak value can reach 33.2% in a specific structure. External electric field has a more significant effect on the CE of uniform-doping GaN NWAs. The solutions provided in this study can make the GaN NWAs photocathode more suitable for the strict requirements of vacuum electron sources